Use of Polymer Inclusion Membrane for the Separation of Phenols Compounds Mixture from Dilute Aqueous Solutions - Balahouane, Abdelghani Mounir; Belfar, Mohamed Lakhdar; Moussaoui, Yacine; Benosmane, Nadjib (International Journal of Membrane Science and Technology, 2022)
Abstract: Separation of phenolic compounds mixture namely: phenol, resorcinol, Bisphenol A from dilute aqueous solutions by polymer inclusion membrane using Cellulose triacetate (CTA) as support was investigated as a means of recovering Bisphenol A from mixture of phenolic compounds. The effects of parameters influencing the separation performance were studied in terms of permeation flux and selectivity. For competitive transport of phenols across PIM with RC8 + NPOE, the selectivity order was Bisphenol > Phenol > Resorcinol. The high permselectivity of the membrane to Bisphenol A was primarily due to its high affinity towards calixresorcinarene macrocycle. This is of particular interest from an industrial point of view because the enriched phenol permeate can be easily recovered upon phase separation. The prepared PIM were characterized by using Raman spectroscopy, XPS and scanning electron microscopy (SEM) techniques. Keywords: PIM, CTA, Membrane separation, Phenols mixture, Bisphenol A, Wastewater treatment.